The Relationship Between Military Expenditures, Democracy and Economic Development: Military Expenditures, Democracy and Economic Development Relationship - Gül, Ekrem; Torusdag, Mustafa (International Journal of Contemporary Economics and Administrative Sciences, 2019)
From the 1950s and onwards, the relationship between democracy and economic development remains a matter of curiosity. In this study, the relationship between democracy and economic development as institutional determinants of military expenditures is investigated by Dumitreschu-Hurlin (2012) time-varying panel causality test for 34 OECD countries for the period of 1990-2017. As a result of the analysis, between 1995-2015 period there was a two-waycausal relationship between military expenditures and economic development, military expenditures and democracy, and a one-way causality running from development to democracy. In the period between 2002 and 2016, there was a one-way causal relationship from democracy to military spending and from democracy to development. In the period of 2003-2017, it was revealed that there was a one way causality from democracy to development and the compatibility perspective is valid.